2005
DOI: 10.1007/s10388-005-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microvascular patterns of superficial esophageal cancers by magnifying endoscopy

Abstract: Background. Endoscopic findings have traditionally been evaluated on the basis of differences in color and changes in surface structure. We examined whether microvascular patterns on magnifying endoscopy could be used to diagnose benign and malignant superficial esophageal lesions and to estimate the depth of tumor invasion. Methods. Magnifying endoscopic findings were compared with histopathological features for 405 superficial lesions arising in the esophagus, including 191 esophageal cancers. Results. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 5 publications
3
113
1
Order By: Relevance
“…SM2 was evident in 55.9% and lym- phovascular involvements were detected in 39.5% of the patients. The accuracy of the diagnostic performance before ESD was 60.4%, which was lower than previous reports (22)(23)(24). The reason for the misdiagnosis of many cases in the present study was that the macroscopic appearance of the tumor influenced the tumor depth of invasion; it remains exceedingly difficult to differentiate between mucosal and sub-mucosal lesions.…”
Section: Discussioncontrasting
confidence: 82%
“…SM2 was evident in 55.9% and lym- phovascular involvements were detected in 39.5% of the patients. The accuracy of the diagnostic performance before ESD was 60.4%, which was lower than previous reports (22)(23)(24). The reason for the misdiagnosis of many cases in the present study was that the macroscopic appearance of the tumor influenced the tumor depth of invasion; it remains exceedingly difficult to differentiate between mucosal and sub-mucosal lesions.…”
Section: Discussioncontrasting
confidence: 82%
“…Recently, magnifying endoscopy has been used to determine tumor depth, as well. 26,27) It is difficult to judge the depth of invasion of esophageal cancer using FDG-PET. 10,28,29) Kato et al reported the detection rate of primary tumor for each depth of invasion (T1-T4).…”
Section: Primary Lesionmentioning
confidence: 99%
“…1c), and IPCL type V -3 in IPCL classification by Inoue 2) in the elevated area (Fig. 1d), but it revealed no type 4R vessels corresponding to poorly differentiated carcinoma or specific histologic type of carcinoma in classification of microvascular pattern by Arima et al 3) IPCL type V -3 showed that the depth of tumor invasion was the muscularis mucosa or slight submucosa. Computer tomography (CT) of the chest and abdomen showed neither lymph node nor distant metastasis.…”
Section: Case Reportmentioning
confidence: 86%
“…Similarly to our case, three of the four cases in which ER had been conducted failed to reach any diagnosis of ECC before the treatment, which suggests that a diagnosis of ECC before treatment is difficult. Arima et al 3) reported that lesions including the type 4R blood vessel, which does not form an avascular area according to classification of the microvascular pattern, includes a specific histologic type esophageal cancer such as ECC. Ozawa et al 5) reported one case observed using magnifying endoscopy with NBI as superficial esophageal ECC, which is described as appearing like type 4R.…”
Section: Case Reportmentioning
confidence: 99%